PELATIHAN PENGGUNAAN E-RUBRIK ASESMEN UNTUK PENINGKATAN KOMPETENSI GURU DI SMK AKOMODASI PERHOTELAN KOTA BANDUNG - Yoyoh Jubaedah; Neni Rohaeni; Nenden Rani Rinekasari; Tati Tati (Lentera Karya Edukasi, 2021)
Abstract: Efforts are needed to help improve the competence of vocational school teachers in hospitality accommodation following the demands of teacher competence. The solution to the problem solving will be training in the use of assessment e-rubrics to increase teacher competence at the Hospitality Accommodation Vocational School. The reason is that the teachers who teach in the Hospitality Accommodation Expertise Vocational School are generally not graduates from the institute of teaching staff but hotel practitioners. Learning experience efforts are needed in using the assessment e-rubric to improve the competence of professional teachers. This assessment rubric aims to measure the competence of students in cognitive, affective, and psychomotor aspects. This program is a reflection for teachers who can apply their skill competencies in using assessment e-rubrics. Teachers can measure the achievement of learning outcomes and student competencies under Hotel SOPs. Thus, this program can improve the professionalism of SMK teachers in the Hospitality Accommodation Expertise. Community Service Activities are carried out through a learning by doing's approach and the lecture method, question, and answer, demonstration, practice. The training activities are 1) Increased knowledge and skills of teachers in designing assessment e-rubrics for the subjects taught, 2) Implementation of teacher competency improvement programs through training in the use of assessment e-rubrics on hotel accommodation competencies. The implication of this activity is the improvement of professional teachers at the Hospitality Accommodation of Vocational School.).Abstrak: Diperlukan upaya untuk membantu peningkatan kompetensi guru SMK Bidang Keahlian Akomodasi Perhotelan yang sesuai dengan tuntutan kompetensi guru. Solusi pemecahan masalah akan dilakukan pelatihan penggunaan e-rubrik asesmen untuk peningkatan kompetensi guru di SMK Akomodasi Perhotelan. Penyebabnya karena guru yang mengajar di SMK Bidang Keahlian Akomodasi Perhotelan umumnya bukan lulusan dari Lembaga Pendidikan Tenaga Kependidikan tetapi dari praktisi hotel. Diperlukan upaya pengalaman belajar di dalam menggunakan e-rubrik asesmen untuk meningkatkan kompetensi guru yang profesional.  Rubrik asesmen ini bertujuan untuk dapat mengukur kompetensi peserta didik pada aspek kognitif, afektif dan psikomotor. Program ini sebagai salah satu refleksi bagi guru yang dapat menerapkan kompetensi keahliannya di dalam menggunakan e-rubrik asesmen. Guru dapat mengukur capaian hasil belajar dan kompetensi peserta didik yang sesuai dengan SOP Hotel. Dengan demikian, program ini dapat meningkatkan profesionalisme guru SMK Bidang Keahlian Akomodasi Perhotelan. Kegiatan Pengabdian Kepada Masyarakat dilakukan melalui pendekatan learning by doing dan metode ceramah, tanya jawab, demonstrasi, Praktik. Hasil dari kegiatan pelatihan yaitu: 1) Meningkatnya pengetahuan dan keterampilan guru dalam merancang e-rubrik asesmen pada mata pelajaran yang diampu, 2) Terimplementasikannya  program peningkatan kompetensi guru melalui pelatihan penggunaan e-rubrik asesmen pada kompetensi akomodasi perhotelan. Implikasi kegiatan ini adalah peningkatan guru profesional di SMK Akomodasi Perhotelan.Keywords: Training, Assessment E-Rubric, teacher competence, Vocational High SchoolKata kunci: Pelatihan, E-Rubrik Asesmen, kompetensi guru, SMK, Akomodasi Perhotelan